Book Review: Innovation and Planned Economy? Technological Change in Centrally Planned Economies: the Examples of the German Democratic Republic and the People’s Republic of Poland - Janicki, Tadeusz (Studia Historiae Oeconomicae, 2025)
The subject of this review is Falk Flade's monograph devoted to the mechanisms of innovation in the planned economies of German Democratic Republic and the People's Republic of Poland. The author combines the concepts of National Innovation Systems and Sectoral Innovation Systems with a comparative approach to analyse two key branches of the economy, microelectronics and synthetic fibre chemistry, in terms of innovation creation in a planned economy. Flade argues that planning did not preclude innovation, but significantly distorted it, replacing competitive incentives with requirements to comply with the plan as well as political and propaganda objectives. Based on extensive archival research, Flade identifies structural barriers that stifled innovation, knowledge diffusion and productivity. Discussing the differences between the GDR and the Polish People's Republic, Flade concludes that they did not result from ideological differences, but from economic management practices and the nature of the relationship between science and industry. The monograph makes an important contribution to economic history and innovation policy studies, offering a nuanced, empirically documented interpretation of ‘planned progress’ in Central and Eastern Europe.